Incidence of vaginal breech delivery in singleton in Siriraj Hospital - Thanyarat Wongwananuruk (2018)
Objective: To determine the incidence of vaginal breech delivery at Siriraj Hospital and to evaluate factor affecting mode of delivery. Design: Cross-sectional study. Setting: Department of Obstetrics and Gynecology, Faculty of Medicine Siriraj Hospital, Mahidol University. Subject: A total of 317 women with singleton breech presentation, ≥ 28 weeks of gestation, who had their deliveries at Siriraj Hospital during January 1st to December 31st 2003. Material and Method: The medical records of these women were reviewed to determine the incidence of vaginal breech delivery. Characteristics regarding current pregnancy and delivery and maternal and fetal outcomes were evaluated, including parity, gestational age, estimate fetal weight, cervical dilation, membranes status, maternal complications, types of breech presentation, and being a private case. Results: The incidence of vaginal breech delivery among these women was 17.7%. Univariate analysis showed that multiparity, gestational age of ≤ 32 weeks, estimate fetal weight of ≤ 2500 grams, advanced cervical dilatation, ruptured membranes, and not being a private case increased the risk of vaginal breech delivery. Multiple logistic regression analysis demonstrated that only advanced cervical dilatation (4-7 cm, adjusted OR 10.7, 95% CI 3.5-33.0; > 7 cm adjusted OR 40.4, 95% CI 12.6-129.2), ruptured membranes (adjusted OR 2.9, 95% CI 1.3-6.3), multiparity (adjusted OR 6.4, 95% CI 2.6-15.7), and gestational age < 32 weeks (adjusted OR 9.7, 95% CI 2.7-35.7) were independently associated with vaginal breech delivery. However, lower apgar scores and neonatal complications, especially prematurity, were more frequent in vaginal than cesarean delivery. Conclusion: Vaginal breech delivery was found in 17.7% of singleton breech presentation in Siriraj Hospital. Certain characteristics during labor and delivery were associated with mode of delivery including advanced cervical dilatation, ruptured membranes, multiparity, and preterm gestational age.